1993
DOI: 10.1046/j.1365-313x.1993.t01-11-00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an asparagus intracellular PR gene (AoPR1) wound‐responsive promoter by the inverse polymerase chain reaction and its characterization in transgenic tobacco

Abstract: SummaryThe Asparagus officinalis intracellular PR1 (AoPRl) gene is expressed in response to wounding and pathogen attack. We utilized the inverse polymerase chain reaction (IPCR) to isolate the cis-acting regulatory sequences of the AoPRl gene following unsuccessful attempts to identify hybridizing clones in genomic libraries. Sequence analysis of two IPCR products revealed that a 347 bp intron was present in the AoPRl gene and that it was probable that the AoPR7 regulatory sequence had been amplified. To test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 44 publications
2
73
0
Order By: Relevance
“…The element was positioned next to the Ac-Tpa gene fused to the asparagus (Asparagus officinalis) Pr1 (AoPr1) promoter. By rapidly responding to both wounding and infection (Warner et al, 1993), the AoPr1 promoter was expected to drive early Tpa gene expression and allow Ds excision prior to T-DNA degradation. To select against stable T-DNA integration, an expression cassette for the negative selectable marker gene cytosine deaminase (codA) was placed on the other side of Ds.…”
Section: Production Of Transformed Plantsmentioning
confidence: 99%
“…The element was positioned next to the Ac-Tpa gene fused to the asparagus (Asparagus officinalis) Pr1 (AoPr1) promoter. By rapidly responding to both wounding and infection (Warner et al, 1993), the AoPr1 promoter was expected to drive early Tpa gene expression and allow Ds excision prior to T-DNA degradation. To select against stable T-DNA integration, an expression cassette for the negative selectable marker gene cytosine deaminase (codA) was placed on the other side of Ds.…”
Section: Production Of Transformed Plantsmentioning
confidence: 99%
“…Recent work in this laboratory on AoPR-1, an intracellular PR protein of Asparagus officinalis (Warner et al, 1992(Warner et al, , 1993) has shown that it is possible to separate the effects of H202 and SA on the induction of defence responses (Mur et al, manuscript submitted). As noted previously (Figure 3a), H202 is a relatively weak inducer of endogenous PR-la expression.…”
Section: Local Expression Of Pr Proteins Is Induced To Suboptimal Levmentioning
confidence: 99%
“…Transgenic tobacco lines used were all T 2 generation derived as described by Warner et al (1993). Chemical treatment of tobacco leaf material involved either injection of intercellular leaf spaces in planta with a 2 ml syringe fitted with a 27G needle, or utilized 1.5 cm diameter leaf discs cored with a cork-borer and treated in Multi-Well dishes (Nunc).…”
Section: Plant Growth Conditions and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of PR-10 proteins and development of transgenic plants overexpressing PR-10 proteins is important step in this direction. Table 1 lists the PR-10 genes which have been used to develop transgenic plants in different crop species [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110]. Multi-location field trials of transgenic plants expressing PR-10 will likely be next step for further evaluation.…”
Section: Pr-10 Proteins: a Resource For Crop Improvementmentioning
confidence: 99%